(untitled) (Vietnam Journal of Community Medicine, 2026)
Transcatheter arterial chemoembolization (TACE) is a widely used therapeutic modality for the treatment of hepatocellular carcinoma. Diaphragmatic necrosis and perforation represent extremely rare complications, with only a few clinical cases reported in the literature. We report a case of a 73-year-old male patient who was admitted with high-grade fever three weeks after undergoing TACE via the right inferior phrenic artery. Imaging findings were suggestive of a hepatic abscess and a pulmonary abscess, suspected to be secondary to right diaphragmatic perforation. The patient was successfully treated with image-guided percutaneous drainage of both hepatic and pulmonary abscesses, in combination with prolonged antibiotic therapy for eight weeks, resulting in complete clinical recovery. This case highlights the importance of careful evaluation of medical and interventional history, early recognition of rare complications, and timely implementation of appropriate therapeutic strategies.